Edukasi Kesehatan Fisik dan Mental tentang Manfaat Vitamin dari Buah dan Sayuran terhadap Tubuh di Panti Asuhan Kota Palembang - Mangunsong, Sonlimar; Simamora, Sarmalina; Puspitasari, Lia; Aguscik, Aguscik (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2025)
This Community Service Activity (Pengabmas) aims to improve the welfare and quality of life of children in orphanages through social service activities. The program includes providing aid for basic needs, health education, and psychosocial activities aimed at enhancing the mental and social wellbeing of the children in the orphanage. The method used in this activity is a participatory approach involving the residents of the orphanage, the management, and volunteers to ensure the sustainability of the program. The results show that providing aid and health education has a positive impact in raising awareness of healthy living habits and the welfare of the children. The evaluation of this activity indicates that the sustainability of the program can be improved through collaboration with various parties, including the government and the private sector.